Molecular heterogeneity of heat-labile enterotoxins from human and porcine enterotoxigenic Escherichia coli. - Tsuji, T (1982)
The heat-labile enterotoxins produced by human enterotoxigenic Escherichia coli (LTh) and porcine enterotoxigenic E. coli (LTp) were purified to homogeneity, and their molecular properties were compared with those of purified cholera enterotoxin (CT). On polyacrylamide gel disk electrophoresis without sodium dodecyl sulfate, LTh, LTp, and CT differed in mobility, suggesting differences in their ionic charges. The pI values of LTh, LTp, and CT were 7.50, 8.10, and 6.80, respectively. On sodium dodecyl sulfate-polyacrylamide gel slab electrophoresis, the B subunit and A1 and A2 fragments of LTh, LTp, and CT differed in mobility, suggesting that they differed in molecular size. Their molecular sizes seemed to decrease in the following order: B subunit, LTh greater than LTp congruent to CT; A1 fragment, LTp greater than LTh congruent to CT; A2 fragment, LTh congruent to CT greater than LTp. Amino acid compositions of LTh, LTp, and CT were also compared.